2022
DOI: 10.3389/fpls.2022.1012583
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of plant-expression system for production of recombinant anti-human IgE: An alternative production platform for therapeutic monoclonal antibodies

Abstract: Omalizumab, the anti-immunoglobulin IgE antibody is the only approved and available monoclonal antibody as an auxiliary medicament for the severe respiratory allergic reactions. It forms small size immune complexes by binding to free IgE, thereby inhibiting the interaction of IgE with its receptors. Additionally, the anti-IgE can also differently shape the airflow by impeding the stimulation of IgE receptors present on structural cells in the respiratory tract. The present study aimed to use plants as an expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…2 ). Previous studies reported that the highest yield of various transiently expressed proteins in N. benthamiana at 6 dpi for anti-PD-L1 (atezolizumab) (86.76 µg/g) 56 , anti-IgE (omalizumab) (41.2 µg/g) 57 , B38 (4 µg/g), and H4 mAb (35 µg/g) 35 . Other plant produced proteins expressed showed yields of 18.49 mg/kg of human interleukin-6 58 , 3 mg/kg of cocaine-hydrolase Fc protein 59 , 730 mg/kg of CMG2-Fc protein 60 .…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Previous studies reported that the highest yield of various transiently expressed proteins in N. benthamiana at 6 dpi for anti-PD-L1 (atezolizumab) (86.76 µg/g) 56 , anti-IgE (omalizumab) (41.2 µg/g) 57 , B38 (4 µg/g), and H4 mAb (35 µg/g) 35 . Other plant produced proteins expressed showed yields of 18.49 mg/kg of human interleukin-6 58 , 3 mg/kg of cocaine-hydrolase Fc protein 59 , 730 mg/kg of CMG2-Fc protein 60 .…”
Section: Discussionmentioning
confidence: 99%